Consumer credit reporting data - Christa Gibbs; Benedict Guttman-Kenney; Donghoon Lee; Scott Nelson; Wilbert van der Klaauw; Jialan Wang (Federal Reserve Bank of New York, 2024)
Since the 2000s, economists across fields have increasingly used consumer credit reporting data for research. We introduce readers to the economics of and the institutional details of these data. Using examples from the literature, we provide practical guidance on how to use these data to construct economic measures of borrowing, consumption, credit access, financial distress, and geographic mobility. We explain what credit scores measure, and why. We highlight how researchers can access credit reporting data via existing datasets or by creating new datasets, including by linking credit reporting data with surveys and external datasets.
Keywords: D10; D82; E21; G50; H31; 330; consumer credit reporting data; credit bureaus; measurement; credit scores; asymmetric information; household finance